2020
DOI: 10.1021/acsomega.0c01693
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered Graphene Oxide Microcomposites Containing Metabolically Versatile Paracoccus sp. MKU1 for Enhanced Catechol Degradation

Abstract: Paracoccus sp . MKU1, a metabolically versatile bacterium that encompasses diverse metabolic pathways in its genome for the degradation of aromatic compounds, was investigated for catechol bioremediation here for the first time to our knowledge. Paracoccus sp. MKU1 degraded catechol at an optimal pH of 7.5 and a temperature of 37 °C, wherein 100 mg/L catechol was completely mineralized in 96 h but required 192 h for complete mineralization of 500 mg/L catechol. While investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Paracoccus sp. MKU1 is metabolically versatile bacteria that possess higher flexibility in utilizing wide range of recalcitrant xenobiotics ( Aravind et al, 2020 ). Genome analysis of Paracoccus sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Paracoccus sp. MKU1 is metabolically versatile bacteria that possess higher flexibility in utilizing wide range of recalcitrant xenobiotics ( Aravind et al, 2020 ). Genome analysis of Paracoccus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the expression of gene clusters corresponding to intradiol ( C12O ) and extradiol cleavage ( C23O ) at the transcriptional levels were found to be constitutive in Paracoccus sp. MKU1 and their expressions were significantly induced in the presence of catechol in a concentration dependent manner ( Aravind et al, 2020 ). The wild-type Paracoccus sp.…”
Section: Introductionmentioning
confidence: 99%
“…The strains BL-YJ10_15-29 ( P. pueri THG-N2.35, 98.98%) and GP-YJ15-74 ( Pseudomonas koreensis Ps 9-14, 98.80%) presented better antimicrobial activity. Although there have been many reports on genus Paracoccus , most of them have focused on its bioremediate aromatic compounds such as pyrene, halobenzoate, and pyridine; there are few reports about its antimicrobial activity ( Aravind et al, 2020 ; Nakkeeran et al, 2021 ). Therefore, more attention should be paid to the antibacterial activity of this genus in the future.…”
Section: Discussionmentioning
confidence: 99%
“…BZD-33 (Ke et al, 2019), Pseudomonas aeruginosa PDM (Al-Asoufi et al, 2017;Khleifat et al, 2019), Rhodococcus UKMP-5M (Suhaila et al, 2019). It has been observed that many of the oxygenase enzymes and the bacteria that harbor them are able to biodegrade different types of aromatic compounds as a substrate (Aravind et al, 2020;Khleifat et al, 2019;Mohite, 2015;Zou et al, 2018). It should be noted that many previous studies emphasized the necessity of providing an optimal amount of carbon and nitrogen sources such as yeast extract, to obtain the maximal rate of biodegradation of phenol or any other organic compounds.…”
Section: Gc Analysismentioning
confidence: 99%